Geoquímica orgânica e estratigrafia de sequências da Bacia do Ceará: uma abordagem integrada para compreender as rochas geradoras e sua evolução paleoambiental - Souza, Ana Clara Braga de (2021)
The Ceará Basin is an offshore basin and belongs to the Brazilian Equatorial Margin, covering the states of Ceará, Piauí, and part of Maranhão. The tectonic evolution of the Ceará Basin is correlated to three stages of sedimentary filling divided in sequence: Sin-rift, represented by the Mundaú Fm, transitional (breakup sequence), represented by the Paracuru Fm. Paracuru and drift (open sea), represented by Fm. Ubarana, Tibau and Guamaré. The deposition of these sequences occurs associated with distinct tectonostratigraphic and geochemical characteristics. Each of these sequences’points to a greater or lesser influence of tectonics, sedimentary input, climatic and eustatic changes, which control the sediment stacking in a basin. Sequence stratigraphy, in turn, was the method employed to investigate these controls. The thesis aims to discuss the basin fill controls and the influence of regressive/transgressive cycles, based on data from reflection seismic interpretation (2D and 3D), geochemical data, and well logging. Additionally, organic matter deposition and preservation and climatic, tectonic, and eustatic changes were evaluated from a geochemical approach. The integrated geochemical methods wereorganic carbon content (TOC), Rock-Eval pyrolysis (RE), and vitrinite reflectance (Ro). The relative hydrocarbon potential (RHP = S1 + S2/TOC) stands out among the indices calculated based on pyrolysis values. The RHP helped in the interpretation of the oxygenation conditions in the Ceará Basin. In conclusion, understanding sequence stratigraphy and understanding this interaction concerning organically enriched rocks provides a better understanding of the depositional systems at work, besides being a powerful tool not only for regional and local stratigraphic correlations but also for stratigraphic intervals of high complexity and delimitation of intervals favorable for organic matter preservation, generation, and storage of hydrocarbons.